Diseño de un dosificador automatico de baquelita para dos tipos diferentes de licuadoras para la Empresa Nacional de Licuadoras Naliet S.A.S. (2019)
The project was carried out by analyzing the molding process, evaluating product development times to parameterize the operation of the dispenser. Design alternatives were proposed based on the dosing systems used in the industry, these alternatives were evaluated, and finally the most suitable for the process and easily adapted to the molding press of the company was chosen. A detailed design was made, the corresponding calculations of each component and operation of the devices involved in the dispenser were made, it was simulated by means of the software, and finally they were evaluated for later validation. Once the corresponding calculations were obtained, the manufacturing, assembly, assembly, plant location and automation plans were prepared with their respective operation, assembly and maintenance manuals. Finally, the financial and environmental study that produces this dosing machine was made.